2022
DOI: 10.1002/anie.202213659
|View full text |Cite
|
Sign up to set email alerts
|

Native Amide‐Directed C(sp3)−H Amidation Enabled by Electron‐Deficient RhIII Catalyst and Electron‐Deficient 2‐Pyridone Ligand

Abstract: Trivalent group-9 metal catalysts with a cyclopentadienyl-type ligand (CpM III ; M = Co, Rh, Ir, Cp = cyclopentadienyl) have been widely used for directed CÀ H functionalizations, albeit that their application to challenging C(sp 3 )À H functionalizations suffers from the limitations of the available directing groups. In this report, we describe directed C(sp 3 )À H amidation reactions of simple amide substrates with a variety of substituents. The combination of an electron-deficient Cp E Rh catalyst (Cp E = 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 95 publications
0
2
0
Order By: Relevance
“…Kim and co-workers realized a directing group-assisted nickel-catalyzed intermolecular C­(sp 3 )-H amidation of carboxamides using TsN 3 as a nitrogen source as well as an internal oxidant (Scheme e) . Wakikawa and co-workers demonstrated that the combination of an electron-deficient Rh­(III) catalyst and an electron-deficient 2-pyridone ligand enabled amide-directed C­(sp 3 )-H amidation reactions using dioxazolone as a nitrogen source (Scheme e) . Alternatively, ring opening of β-lactams, oxazoles, or pyrazolones was reported to afford various β-aminoamides .…”
Section: Introductionmentioning
confidence: 99%
“…Kim and co-workers realized a directing group-assisted nickel-catalyzed intermolecular C­(sp 3 )-H amidation of carboxamides using TsN 3 as a nitrogen source as well as an internal oxidant (Scheme e) . Wakikawa and co-workers demonstrated that the combination of an electron-deficient Rh­(III) catalyst and an electron-deficient 2-pyridone ligand enabled amide-directed C­(sp 3 )-H amidation reactions using dioxazolone as a nitrogen source (Scheme e) . Alternatively, ring opening of β-lactams, oxazoles, or pyrazolones was reported to afford various β-aminoamides .…”
Section: Introductionmentioning
confidence: 99%
“…Driven by the prevalence of alkyl amines in a myriad of biologically relevant molecules and preclinical candidates, we wondered whether we could establish “ a la carte ” site-selective interrupted Ni-catalyzed deaminative chain-walking for forging sp 3 –sp 3 linkages at the always elusive methylene sp 3 C–H bonds with predictable and tunable selectivity by using weakly coordinating native amides (Scheme , bottom) . The choice of the latter is not arbitrary, as these ubiquitous motifs possess an electron-rich carbonyl fragment suitable for metal chelation without the need for decorating the amide backbone with strongly chelating quinoline or pyridine backbones, hence setting the basis for applying these techniques to advanced synthetic intermediates . As part of our interest in the field, we report herein the successful realization of this goal.…”
mentioning
confidence: 99%